II Internationale Biennale der Papierkunst : Papier macht raum - Eimert, Dorothea; Reichardt, Jasia (Düren : Leopold-Hoesch-Museum, 1988)
Riedl, Josef Anton ; Antes, Horst ; Atkinson, Marea ; Ammon, Elisabeth ; Balsgaard, Jane ; Barker, Laurence ; Becker, Helmut ; Beckers, Günther ; Brüning, Stefanie ; Capone, Vito ; Cho, Sung Mook ; Covrig, Doru ; Daquin, Pierre ; Dawson, Sophia ; Ebbesen, Torben et al.
II Internationale Biennale der Papierkunst : Papier macht raum, Leopold-Hoesch-Museum, Düren, 12.6 - 28.8.1988
boek